Beginning C : From Beginner to Pro - Gonzalez-Morris, German; Horton, Ivor (Apress L.P., 2020)
Learn how to program using C, beginning from first principles and progressing through step-by-step examples to become a competent, C-language programmer. All you need are this book and any of the widely available C compilers, and you'll soon be writing real C programs. Youll discover that C is a foundation language that every programmer ought to know. Beginning C is written by renowned author Ivor Horton and expert programmer German Gonzalez-Morris. This book increases your programming expertise by guiding you through the development of fully working C applications that use what you've learned in a practical context. Youll also be able to strike out on your own by trying the exercises included at the end of each chapter. At the end of the book you'll be confident in your skills with all facets of the widely-used and powerful C language. You will: Discover the C programming language Program using C starting with first steps, then making decisions Use loops, arrays, strings, text, pointers, functions, I/O, and more Code applications with strings and text Structure your programs efficiently Work with data, files, facilities, and more.